Minerals - MDPI (MDPI, 2026)
Minerals is an international, peer-reviewed, open access journal of natural mineral systems, mineral resources, mining, and mineral processing, and is published monthly online by MDPI.
Keywords: Mineralogía; Geología; Revistas depredadoras; Predatory journals